SISTEM PENGENDALIAN PEMESANAN BAHAN BAKU SUSU BUBUK SERTA KEBIJAKANNYA - Deden Jaelani; Darmawan Yudhanegara (Industrika : Jurnal Ilmiah Teknik Industri, 2021)
Formula milk production companies are faced with an optimal ordering control system. The availability of raw materials is a measure of the performance of the ordering system at a low cost. This research was conducted to determine the optimal order point with a minimum ordering cost. Ordering decision making is considered from company policy because of the budget. The results of this study indicate that the frequency of purchasing raw materials is 9 times the purchase of raw materials in one year period, 12 times a year of policy. The total purchase of raw material inventories was Rp. 48,671,774, and the policy was Rp. 50,765,157.35 per year. The savings in ordering costs amounted to Rp. 2,093,383.35. The reorder point is 5,634 pcs.